The Effects of Permanent Technology Shocks on Labor Productivity and Hours in the RBC model - Jesper Lindé (Sveriges Riksbank, 2004)
Recent work on the effects of permanent technology shocks argue that the basic RBC model cannot account for a negative correlation between hours worked and labor productivity. In this paper, I show that this conjecture is not necessarily correct. In the basic RBC model, I find that hours worked fall and labor productivity rises after a positive permanent technology shock once one allows for the possibility that the process for the permanent technology shock is slightly persistent in growth rates. A more serious limitation of the RBC model is its inability to generate a persistent rise in hours worked after a positive permanent technology shock along with a rise in labor productivity that are in line with what the data suggests. These results call for a reconsideration of the real and nominal frictions and policy response that need to be introduced in the basic RBC model in order to improve the models ability to match the data.
Keywords: E24; E32; 330; permanent technology shocks; hours worked per capita; labor productivity; real business cycle model; vector autoregressions